EFFECTIVENESS OF ANNEALING TREATMENT AND POLYMER BLENDS ON I-V CHARACTERISTSICS OF POLYMER SOLAR CELL - Erlyta Septa Rosa; Shobih Shobih (Dept. of Chemical Engineering, Diponegoro University, 2013)
This research reports on a fabrication of polymer solar cells based on blends of two widely used polymeric semiconductors i.e. poly(2-methoxy-5-(3,7-dimethyloctyloxy)-para phenylene vinylene) (MDMO-PPV) and the soluble fullerene C60 derivative [6,6 phenyl C61-butyric acid methyl ester] (PCBM). The devices were fabricated on an indium tin oxide (ITO) coated glass substrate. After cleaned and dried, a poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) in H2O was spin coated onto the freshly prepared substrate and then dried in a vacuum oven at 120°C for 60 minutes. A blend of MDMO-PPV and PCBM in chlorobenzene was spin coated on the top and dried in a nitrogen ambient at room temperature for 24 hours. The devices were transferred to a sputtering system where an aluminum was coated. Some of the devices then were annealed in a vacuum oven at 60°C for 60 minutes. Finally, the devices were encapsulated by placing a sealant between the back of the devices and glass slides and then cured in a vacuum oven at temperature 100°C for 10 minutes. For characterization, the devices were illuminated with a xenon lamp at the intensity of 27 mW/cm2 and the temperature at approximately 25°C. The influence of the annealing treatment and polymer blends on the photovoltaic performance of the devices was also discussed here. The best performance was obtained from the device with a blend ratio of 1:1 MDMO-PPV/PCBM without annealing treatment. The typical power efficiency was 0.01% with open circuit voltage of 0.347 V, short circuit current of 0.064 mA, and maximum power of 0.006 mW.